Monitoring agricultural drought based on optical remote sensing data - Mozomdar, Abdur Rahim; Jahan, Noshin Nawar; Roni, Rezaul (Bulletin of Geography. Physical Geography Series, 2026)
Agricultural drought is a result of prolonged rainfall deficits affecting rice productivity. Agriculturally dependent regions are more vulnerable to agricultural drought. Therefore, drought monitoring is essential for effective agricultural management. This study aimed to investigate the drought variability of Rajshahi, Bangladesh utilizing optical remote sensing data from Landsat during 2000 to 2024, excluding 2007 due to technical faults in satellite imageries. This drought assessment used the Vegetation Health Index (VHI), which combines the Vegetation Condition Index (VCI) and the Temperature Condition Index (TCI), during pre-monsoon (March–May) and post-monsoon (October–November) seasons. The Standardized Precipitation Evapotranspiration Index (SPEI) was also used for cross-validation of areas affected by meteorological and agricultural drought. This study reveals that the “slightly dry” category of drought was predominant in all the districts for both seasons, where districts like Chapainawabganj, Pabna, Rajshahi and Sirajganj exhibited a significantly higher frequency of “dry” and “slightly dry” drought conditions. The Mann–Kendall test found no statistically significant trend of VHI for 24 years, indicating that drought has no linear pattern of occurrence. The cross-tabulation between SPEI and VHI showed a moderate agreement between drought categories, but a good relationship was found in normal conditions of drought from both indices. This suggests that meteorological drought may not be the only cause of agricultural drought; climate variables and agricultural practice have a great influence too.